PENINGKATAN IKATAN P DALAM KOLOM TANAH GAMBUT YANG DIBERI BAHAN AMELIORAN TANAH MINERAL DAN BEBERAPA JENIS FOSFAT ALAM - W. Hartatik; Komarudin Idris; Supiandi Sabiham; Sri Djuniwati; J. Sri Adiningsih (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
Peat soils have very low capacity in retaining P. Mineral soils rich in Fe could be used as ameliorant in increasing this capacity. The aim of this experiment was to study the use of three rock phosphates and SP-36 on peat amended with mineral soil in increasing P retention. The experiment was conducted in the laboratory of the Centre for Soil and Agroclimate Research and Development, Bogor. P treatments consist of four P fertilizer sources including Morocco rock phosphate, Christmas rock phosphate, Ciamis rock phosphate, and SP-36, and three P level (50, 100 and 200% of P sorption) plus partial and complete control in 2 replications. The experiment conducted in the soil column made from PVC pipe 4 inches in diameter. The column was filled with 1,250 g peat dry weight (10.5 oC), 250 g of which was amended with mineral soil and each of three rock phosphates or SP-36, and put on as the upper part of the column and incubated for 4 weeks. Leaching was conducted every day, with 50 cc distilled water for 12 days. The filtrate was collected in 500 cc Erlenmeyer glass, and soluble P was analyzed. After this step peat in the colu nnw as divided into seven depth that was 0-5, 5-10, 10-20, 20-30, 30-40, 40-50 and 50-60 cm, then P-Bray I was analyzed. The results showed that the application of Morocco and Ciamis rock phosphates on peat amended with mineral soil after leaching, resulting in the accumulation of P on the upper layers, suggesting that P retention on peat was increased such that P loss could be reduced. The ratio of P content in the soil column at 0-30 cm and 30-60 cm depth for Morocco rock phosphate on the dosages of 50, 100 and 200% of P sorption were 1.54; 1.90; and 2.79, respectively, and that for Ciamis rock phosphate were 1.64; 1.76 and 4.11, respectively. The application of Christmas rock phosphate resulted in P accumulation at 30-40 cm depth. The ratio of P content in soil column treated with Christmas rock phosphate at 0-30 cm and 30-60 cm depth on dosages of 50, 100 and 200% of P sorption were 1.05; 1.11 and 1.38, respectively, suggesting that P was leached to the bottom layer. It seems that high Fe in Christmas rock phosphate did not contribute to an increase of P retention. Although the application of SP-36 resulted in P accumulation at the upper layers, P leaching was higher. Keywords: Amelioration, Peat, Phosphorus fertilization, Phosphorus retention